Direct observation of magnetic phase coexistence and magnetization reversal in a Gd0.67Ca0.33MnO3 thin film - Kim, Jeehoon (2012)
We have investigated the ferrimagnetic domain structure in a Gd0.67Ca0.33MnO3 thin film using magnetic force microscopy. We observe clear signs of phase separation, with magnetic islands embedded in a non-magnetic matrix. We also directly visualize the reversal of magnetization of ferrimagnetic domains as a function of temperature and attribute it to a change in the balance of magnetization of anti-aligned Mn and Gd sublattices.